OUTCOMES OF THE FIFTH INTERNATIONAL CONFERENCE ON PEDIATRIC MECHANICAL CIRCULATORY SUPPORT SYSTEMS AND PEDIATRIC CARDIOPULMONARY PERFUSION - Ündar, Akif (2009)
The overall objective of the Conference was to bring together internationally know clinicians, bioengineers, and basic scientists involved in research on pediatric mechanical cardiac support systems and pediatric cardiopulmonary bypass procedures. The primary focus was to explicitly describe the problems with current pediatric mechanical circulatory support systems, methods, and techniques during acute and chronic support. The organizers were able to bring together respected international scholars from over 25 different countries at past conferences that has already made a significant impact on the treatment of pediatric cardiac patients during the past three years. Over 1,300 participants (250–300 participants each year) from many countries, including Argentina, Australia, Austria, Belgium, Brazil, Canada, China, Finland, France, Germany, Greece, Ireland, Italy, Japan, Kuwait, Netherlands, New Zealand, Poland, South Korea, Saudi Arabia, Scotland, Spain, Switzerland, Taiwan, Turkey, the United Kingdom, and the United States, have participated in the 2005, 2006, 2007, 2008, and 2009 events. To date, The Fifth International Conference on Pediatric Mechanical Circulatory Support Systems and Pediatric Cardiopulmonary Perfusion is the only conference solely dedicated to pediatric cardiac devices used during acute and chronic mechanical circulatory support. There is no other national or international conference to precisely define the problems with pediatric cardiac patients, and to suggest solutions with new methodologies and devices for pediatric patients, but specifically for neonates and infants.